Why (suffering) women matter for the heart of transformative missional theology perspectives on empowered women and mission in the New Testament and early Christianity - Kok, Jacobus (HTS teologiese studies, 2016)
In this article, it is argued that from the beginning of the Christ-following movement, the gospelmessage represented a challenge to a male-dominated social system. Early Christian literature shows that women, whose voices were often silenced in antiquity, are empowered. This is seen most clearly in the Martyrdom of Perpetua and Felicity. There we see how the protagonists is presented as acting counter culturally, challenging the world of men and turning patriarchal values and expectations upside down. It could be argued that the gospel message portrays women in the centre of missionary witness and empowers them in this manner. Furthermore, early Christian Martyrdom texts also show how the concept of suffering, honour and shame is redefined and how power and strength in weakness and oppression is reformulated.